Improving the performance and quality of processes by applying and implementing Six Sigma methodology in furniture manufacturing process : Poboljšanje izvedbe i kvalitete procesa proizvodnje namještaja primjenom metodologije Six Sigma - Simanová, Ľubica (Array, 2019)
The main aim of this paper is to illustrate the application of selected methods and procedures in the implementation of the Six Sigma Methodology in the furniture manufacturing processes, specifically in the wood veneer pressing, to verify the application and to evaluate the benefits of using selected methods and procedures through a series of step DMAIC process improvement. The application of selected methods and tools within the Six Sigma Methodology, such as DPMO, efficiency and sigma levels, project charter, histogram of mistakes caused by the application of the adhesive, the SIPOC plot mapping process, reaction plans, Ishikawa diagram and control diagrams bring the system and clarity of measurable results into project management for process improvement and process change. The benefits of their use are the cost savings and performance improvement processes.